Intravoxel Incoherent Motion Magnetic Resonance Imaging for Prediction of Induction Chemotherapy Response in Locally Advanced Hypopharyngeal Carcinoma: Comparison With Model‐Free Dynamic Contrast‐Enhanced Magnetic Resonance Imaging. Issue 1 (11th February 2021) - Guo, Baoliang; Ouyang, Fusheng; Ouyang, Lizhu; Huang, Xiyi; Guo, Tiandi; Lin, Shaojia; Liu, Ziwei; Zhang, Rong; Yang, Shao‐min; Chen, Haixiong; Hu, Qiu‐gen
Abstract : Background: Multiparametric intravoxel incoherent motion (IVIM) provides diffusion and perfusion information for the treatment prediction of cancer. However, the superiority of IVIM over dynamic contrast‐enhanced (DCE) magnetic resonance imaging (MRI) in locally advanced hypopharyngeal carcinoma (LAHC) remains unclear. Purpose: To compare the diagnostic performance of IVIM and model‐free DCE in assessing induction chemotherapy (IC) response in patients with LAHC. Study Type: Prospective. Population: Forty‐two patients with LAHC. Field Strength/Sequence: 3.0 T MRI, including IVIM (12 b values, 0–800 seconds/mm 2 ) with a single‐shot echo planar imaging sequence and DCE‐MRI with a volumetric interpolated breath‐hold examination sequence. IVIM MRI is a commercially available sequence and software for calculation and analysis from vendor. Assessment: The IVIM‐derived parameters (diffusion coefficient [ D ], pseudodiffusion coefficient [ D *], and perfusion fraction [ f ]) and DCE‐derived model‐free parameters (Wash‐in, time to maximum enhancement [Tmax], maximum enhancement [Emax], area under enhancement curve [AUC] over 60 seconds [AUC60 ], and whole area under enhancement curve [AUCw ]) were measured. At the end of IC, patients with complete or partial response were classified as responders according to the Response Evaluation Criteria in Solid Tumors. Statistical Tests: The differences of parameters between responders and nonresponders were assessed using Mann–Whitney U tests. The performance of parameters for predicting IC response was evaluated by the receiver operating characteristic curves. Results: Twenty‐three (54.8%) patients were classified as responders. Compared with nonresponders, the perfusion parameters D *, f, f  ×  D *, and AUCw were significantly higher whereas Wash‐in was lower in responders (all P ‐values <0.05). The f  ×  D * outperformed other parameters, with an AUC of 0.84 (95% confidence interval [CI]: 0.69–0.93), sensitivity of 79.0% (95% CI: 54.4–93.9), and specificity of 82.6% (95% CI: 61.2–95.0). Data Conclusion: The IVIM MRI technique may noninvasively help predict the IC response before treatment in patients with LAHC. Level of Evidence: 2 Technical Efficacy: Stage 2